The Punishment of the Grave: a Neglected Motivation for Jihad and Martyrdom - Karimi, Nima (Perspectives on terrorism, 2023)
This article explores the role of a spiritual punishment unique to Islam, the punishment of the grave, in motivating jihadi terrorism. It argues that the exemption from this spiritual punishment granted to jihadi martyrs may be a ‘pull’ factor in the radicalisation of some Muslims. To date the punishment of the grave has been discussed only in passing in the research literature on jihadist radicalisation. To address the resultant gap in our knowledge, this article describes the concept, documents its neglect in the study of jihadist radicalisation, investigates the prevalence of this concern amongst believers, ranging from the nominally affiliated to violent extremists, and the use of the concept by prominent jihadist figures and organisations to attract and train new martyrs. Arguing that a concern with the punishment of the grave is a crucial but overlooked aspect of the heightened religiosity — and based on its expression perhaps uniquely instrumental in identifying believers left with limited options, including violence — the article advocates recognising it as a significant and useful additional marker of radicalisation, especially in the context of prisons. Increased awareness of the concept and the extraordinary fear it often generates will help to better attune strategies used to prevent and deradicalise individuals to the religious struggles driving some Muslims to sacrifice their lives in lethal acts of terrorism.